Statins and microalbuminuria - Dias, Patrícia (2003)
Microalbuminuria is at present considered an indicator of cardiovascular risk, often occurring associated with other cardiovascular risk factors and might be the renal marker for anincreased endothelial permeability that accompanies the atherogenic process. According tosome studies, the prevalence of microalbuminuria in the general population ranges from 3.8to 14.6%, being higher in diabetic and/or hypertensive individuals.Histopathological and experimental evidence suggest that dyslipidaemia can initiate andcontribute to the progression of nephropathy, with mechanisms similar to those involved inatherosclerosis; on the other hand, urinary albumin loss may lead to a rise in lipoprotein plasmatic levels.Lipid lowering therapy with statins has beenshown to reduce cardiovascular risk and also to improve endothelial function. Animal and invitro experiments have demonstrated beneficial effects of these drugs in several models ofnephropathy, including reductions in urinaryprotein excretion. Some studies conducted in patients with abnormal excretion of urinaryprotein support the hypothesis that reno-protective effects also occur in humans; however,the field is still open for investigation in thisarea, particularly the effect of statins in the reduction of microalbuminuria.